Core statutes on company law - Ervine, Cowan (Macmillan, 2008)
This is an expert selection of statutes relating to company law designed to provide an easy-to-use reference whether in the lecture hall or in the examination. It contains the essential materials students need. It is published annually to ensure content is completely up-to-date. It excludes commentary and is therefore ideal for exam use. It is designed to be easy to use under exam conditions. It is compiled by an experienced lecturer